Pengaruh Kerjasama Tim, Komunikasi Dan Disiplin Kerja Terhadap Kinerja Karyawan SMK Muhammadiyah 1 Rumbia Lampung Tengah, Lampung - Sadam Muklis Saefi; Sakinah Sakinah; Riki Gana Suyatna (Jurnal Bintang Manajemen, 2024)
The aim of this research is to test and analyze the influence of teamwork, communication and work discipline on employee performance at SMK Muhammadiyah 1 Rumbia. This research method is quantitative research and descriptive research. A population of several workers at SMK Muhammadiyah 1 Rumbia participated in this research. Muhammadiyah 1 Vocational School Rumbia, numbering approximately 30 employees using validity and reliability tests. This data analytical model uses multiple regression analysis. The results of the research are also the conclusions of the research. Partial teamwork has a positive and significant influence on the performance of employees at SMK Muhammadiyah 1 Rumbia. One of the impacts is positive and significant communication on the performance of employees at SMK Muhammadiyah 1 Rumbia. Partially, work discipline has a positive and significant effect on employee work results. At the same time, teamwork, communication and work discipline have a positive and significant effect on the work results of employees at SMK Muhammadiyah 1 Rumbia.